Establishing a universal IVRP method for quadrivalent HPV vaccines to replace in vivo potency tests - Jinpan Hu; Zijing Jia; Meng Wang; Lingling Nie; Wangjun Fu; Qingfeng Zhang; Haiyang Qin; Jianhui Nie; Xiaoyu Xu; Lingjie Xu; Fengze Wang; Yingping Chen; et al. (npj Vaccines)
Abstract Several human papillomavirus (HPV) L1-based virus-like particle (VLP) vaccines are in development to meet future global vaccination needs. Type-specific monoclonal antibodies with good reactivity to all types of vaccines are urgently needed to evaluate vaccine potency. In this study, binding activity, neutralizing activity, conformational sensitivity, immunodominance in human serum, and versatility were compared among antibodies. A broad-spectrum binding antibody (C4-F5-127) was selected as the capture antibody; four type-specific neutralizing antibodies (6-F5-77, 11-F5-187, 16-F5-196, and 18-F5-203) were selected as detection antibodies for HPV6, 11, 16, and 18, respectively. These antibodies formed a standardized and universal in vitro relative potency (IVRP) assay kit. High-resolution cryo-electron microscopy (cryo-EM) structures of HPV6-6-F5-77, HPV11-11-F5-187, HPV16-16-F5-196 and HPV18-18-F5-203 complexes define the location and nature of epitopes, revealing serotype specific binding modes and neutralization mechanisms. The IVRP results were correlated with potency data from mouse models, offering an efficient alternative to in vivo potency experiments.